Mastering Collaboration (Audio Book) - Anderson, Gretchen (O'Reilly Media, Inc., 2019)
Collaboration is key for organizations in the 21st century, yet few business people have been trained to teach this skill. How do you advance ideas in a collaborative way and then communicate them throughout your company? In this practical audio book, author Gretchen Anderson shows you how to generate ideas with others while gaining buy-in from all levels of your organization. Product managers, designers, marketers, technical leaders, and executives will obtain better insight into how team members work together to make decisions. Through tangible exercises and techniques, you'll learn how to turn promising ideas into products, services, and solutions that make a real difference in the market. Use a framework to develop ideas into hypotheses to be tested and refined Avoid common pitfalls in the collaboration process Align communication approaches to ensure that collaboration is effective and inclusive Structure events or meetings for different types of collaboration depending on the people involved Practice giving and receiving critiques to foster inclusion without resorting to consensus-based decisions.